An in silico approach to design potential siRNA molecules for ICP22 (US1) gene silencing of different strains of human herpes simplex 1 - Nur, Suza Mohammad (2013)
BACKGROUND: The herpes simplex virus (HSV-1) is a virus that manifests itself in viral infection with painful, watery blisters in the skin or on the genitals as well as mucous membrane such as the mouth or lips. During an outbreak, the disease is contagious particularly and is irredeemable with present technology. Genetic studies of HSV-1 have shown that ICP22 (US1) gene is an immediate early gene and is responsible for genome replication and also has contribution in viral infection. METHOD: For disease diagnosis, ICP22 (US1) gene may be suitable target. Viral activity can be controlled through RNA interference technology, a significant method for the post-transcriptional gene silencing. However, in different viral isolates there is a genetic variability; it is very challenging to design possible siRNA molecules which can silence the respective target genes. The work was done by using various computational tools as similarity search, target alignment, secondary structure prediction and RNA interaction evaluation. RESULT: In our study two effective siRNA molecules for ICP22 (US1) gene silencing of seven different strains of HSV-1 were rationally designed and authenticated using computational methods, which might lead to knockdown the viral activity. CONCLUSION: siRNA molecules were foreseen against ICP22 (US1) gene of different strains of HSV-1 as effective aspirant using computational methods. Thus, the approach may deliver a vision for the chemical synthesis of antiviral RNA molecule for treatment of HSV-1, at genomic level.